2017
DOI: 10.1149/2.0251706jss
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Synthesis Parameters in Carbon Nanotubes Doped with Nitrogen for Oxygen Electroreduction

Abstract: Nitrogen doped carbon nanotubes (N-CNTs) were synthesized by modified chemical vapor deposition method using a novel two steps thermal technique. Pyridine was used as carbon and nitrogen source and ferrocene as catalyst for nanotubes growth. The effects of reactor temperature and carrier gas flow were investigated using scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy and linear scan voltammetry. Results show that the synthesis temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The electrochemical properties of the best test sample also stemmed from the surface structure, due to corrugation, and the extensive distribution of defects, which can act as active sites or cause better access to the edge functional groups. Other researchers, Gonzalez et al [145], used melamine as a source of nitrogen and carbon and ferrocene as a catalyst for the growth of N-doped nanotubes to investigate the electrochemical properties in an acidic environment. As expected, the materials produced at 900 • C exhibited higher ORR activity relative to 800 • C synthesis.…”
Section: Synthesis Of Nitrogen-doped Carbon Nanotube-based Materials ...mentioning
confidence: 99%
“…The electrochemical properties of the best test sample also stemmed from the surface structure, due to corrugation, and the extensive distribution of defects, which can act as active sites or cause better access to the edge functional groups. Other researchers, Gonzalez et al [145], used melamine as a source of nitrogen and carbon and ferrocene as a catalyst for the growth of N-doped nanotubes to investigate the electrochemical properties in an acidic environment. As expected, the materials produced at 900 • C exhibited higher ORR activity relative to 800 • C synthesis.…”
Section: Synthesis Of Nitrogen-doped Carbon Nanotube-based Materials ...mentioning
confidence: 99%
“…They defined this peak as gaseous nitrogen, being intercalated between the CNT shells in the vicinity of an internal cavity of the CNT. In contrast, this peak can also be identified as chemisorbed -NOx species, like a nitro group -NO2 or in form of nitrogen oxides of pyridinic nitrogen [33][34][35][36]. For the proof of nitrogen oxides, we measured the N1s and O1s spectra of freshly synthesized N-MWCNT carpets, which were exposed to air for 1 h. We again obtained the peak at around 405.0 eV, but no clear traces of oxygen (~0.1 at.-%, as shown in supplementary data).…”
Section: Surface Properties Of N-mwcnt Carpetsmentioning
confidence: 99%
“…Kure et al [18] reported modified commercial microwave ovens with quartz tubes to synthesized CNTs from Polyethylene. Gonzalez et al [19] doping carbon nanotubes with Nitrogen from Pyridine/ ferrocene as sources of carbon and catalyst respectively, by modified chemical vapor deposition method using a novel two steps thermal technique. Many literatures such mentions previously, include modified strategy for preparation of complicating causing to increase the cost of preparing in addition to pre-treatment for sources of carbon before use.…”
Section: Introductionmentioning
confidence: 99%